2015
DOI: 10.1074/jbc.m115.654897
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of ERK Kinase by MEK1 Kinase Inhibition in the Brain

Abstract: Background: ERK/MAPK signaling is important in brain function. Results: MEK1 is inhibited by phosphorylation at Thr-292/286 by Cdk5, ERK, and Cdk1. These mechanisms are regulated by striatal glutamate and dopamine neurotransmission and acute stress in vivo. Conclusion: Excitatory and metabotropic neurotransmission converge on MEK1 regulation. Significance: A greater understanding of MEK1/ERK signaling provides insights into brain function, disease, and potential treatment strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 79 publications
1
12
0
Order By: Relevance
“…Studies have shown that CDK5 can alter pain-related neuronal plasticity by regulating ERK1/2 activation in anesthetized rats [15]. CDK5 has also been characterized to phosphorylate the ERK-activating protein kinase MEK1 in the brain [16]. The present results demonstrated that CDK5 promoted renal tubulointerstitial fibrosis through enhancing phosphorylated ERK1/2 and PPARγ in diabetic nephropathy.…”
Section: Discussionsupporting
confidence: 61%
“…Studies have shown that CDK5 can alter pain-related neuronal plasticity by regulating ERK1/2 activation in anesthetized rats [15]. CDK5 has also been characterized to phosphorylate the ERK-activating protein kinase MEK1 in the brain [16]. The present results demonstrated that CDK5 promoted renal tubulointerstitial fibrosis through enhancing phosphorylated ERK1/2 and PPARγ in diabetic nephropathy.…”
Section: Discussionsupporting
confidence: 61%
“…Further, the autophosphorylation of P-loop residues in RAF proteins serves as another feedback mechanism that impairs their kinase activity [234]. For MEK, it can be phosphorylated at its N-terminus that intercepts its activity [235].…”
Section: Feedback Inhibition and Return To The Inactive Statementioning
confidence: 99%
“…MEK1 enzymatic activity is regulated by site-specific phosphorylation that can be activated with phosphorylation of Ser217/Ser221 by Raf kinase 40 or suppressed by phosphorylation of Thr286 and Thr292 by CDK1 and CDK5 38 , 39 , 41 or Thr292 and Thr386 by ERK1/2 42 44 (Fig. 4a ).…”
Section: Resultsmentioning
confidence: 99%